Expression and clinical significance of miR-770-5p and miR-145-5p in patients with diabetic nephropathy - Bing-fei Zhang; Xue Sun (Linchuang shenzangbing zazhi)
Objective To explore the expressions and clinical significance of MicroRNA-770-5p （miR-770-5p） and MicroRNA-145-5p （miR-145-5p） in patients with diabetic kidney disease （DKD）. MethodsFrom December 2020 to December 2022, 132 DKD patients （n = 132） were designated as DKD group, another 132 type 2 diabetes patients （n = 132） as T2DM group and still another 132 health checkups at the same time as control group. Real-time fluorescent quantitative polymerase chain reaction （qRT-PCR） was applied for measuring the serum expression levels of miR-770-5p and miR-145-5p. The prognostic factors of DKD were examined by multiple Logistic regression analysis. And predictive value of serum miR-770-5p and miR-145-5p for DKD prognosis was analyzed through plotting receiver operating characteristic （ROC） curve. Results As compared with control group, the expression levels of serum miR-770-5p and miR-145-5p spiked markedly in T2DM and DKD groups （P＜0.05）. As compared with early DKD group, the serum expression levels of miR-770-5p and miR-145-5p in middle and late DKD groups rose obviously （P＜0.05）. As compared with good prognosis group, the serum expression levels of miR-770-5p and miR-145-5p jumped greatly in poor prognosis group （P＜0.05）. As compared with good prognosis group, there were significant differences in urea nitrogen, albumin and serum creatinine in poor prognosis group （P＜0.05）. Multivariate Logistic results indicated that miR-770-5p, miR-145-5p, urea nitrogen and serum creatinine were risk factors for the prognosis （P＜0.05） while albumin was a protective factor （P＜0.05）. The area under the curve （AUC） of the combined prognostic prediction of serum miR-770-5p and miR-145-5p was the highest. It was better than individual prediction of serum miR-770-5p and miR-145-5p （Z combination - miR-770-5p = 3.632, P = 0.003, Z combination - miR-145-5p = 2.370, P = 0.018）. Conclusions The serum expression levels of miR-770-5p and miR-145-5p are up-regulated in DKD patients. It is closely correlated with the severity and prognosis of DKD. The combination of the two is more valuable in evaluating the prognosis of DKD patients.